2018
DOI: 10.1101/339747
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Oxygen restriction generates difficult-to-culture pathogens

Abstract: 34 35 Keywords: 36 P. aeruginosa biofilm / anoxia / biofilm / reactive oxygen species / difficult-to-culture / viable but non-culturable 37 38 Abstract: 233 words 39 Document: 4604 words 40 Abstract 41Induction of a non-culturable state has been demonstrated for many bacteria. In a clinical 42 perspective, the lack of growth due to these non-culturable bacteria can have major consequences 43 for the diagnosis and treatment of patients. Here we show how anoxic conditioning (restriction of 44 molecular oxygen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…The numerical model suggested that P. aeruginosa grown in alginate beads was associated with higher death rates than the other models. For simplicity, we used the term death rate, but it might better be explained by a switch to an inactive state, as it has previously been shown that bacteria can resume growth after prolonged starvation and electron acceptor depletion (Kvich et al, 2019).…”
Section: Metabolic Differences Between Single Cells and Biofilmsmentioning
confidence: 99%
See 1 more Smart Citation
“…The numerical model suggested that P. aeruginosa grown in alginate beads was associated with higher death rates than the other models. For simplicity, we used the term death rate, but it might better be explained by a switch to an inactive state, as it has previously been shown that bacteria can resume growth after prolonged starvation and electron acceptor depletion (Kvich et al, 2019).…”
Section: Metabolic Differences Between Single Cells and Biofilmsmentioning
confidence: 99%
“…The increased tolerance of biofilms toward antibiotics is frequently attributed to a lower metabolic rate (Kolpen et al, 2017), upregulated efflux pumps (Frimodt-Møller et al, 2018;Bartell et al, 2019), protection by matrix components (Tseng et al, 2013;Cao et al, 2016) or SOS responses (Nguyen et al, 2011;Bernier et al, 2013), and is determined by direct exposure to antibiotics and measure of killing either by plating and enumeration of surviving colony forming units (CFU) or live/dead staining. The CFU method, however, can be slow and prone to biases, such as counting aggregates as single CFUs or false negatives due to the induction of viable but non-culturable state of the bacteria (Kvich et al, 2019). Similarly, live/dead staining may overestimate the proportion of dead cells, due to the binding of propidium iodide to eDNA (Rosenberg et al, 2019).…”
Section: Introductionmentioning
confidence: 99%